1935
DOI: 10.1037/h0093362
|View full text |Cite
|
Sign up to set email alerts
|

The development of Alfred Binet's psychology.

Abstract: Thanks are due to my parents and to those persons whose financial aid made possible these studies. And thanks are due to Professor Frank S. Freeman of Cornell University for his constant encouragement and his unwearying patience. CONTENTSChapter I. Binet as an Associationist Chapter II. The Transitional Period Chapter III. Individual Psychology Chapter IV. The Invention of the Scale and Its Use. The Evolution of a New System of Psychology Chapter V. Conclusion 115 Bibliography CHAPTER IBlNET AS AN ASSOCIATIONI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Binel (Varon, 1935) slarted oul using tests of basic perceptual and cognitive capacities to measure IQ, but found large practice effects, which were later documented by Gibson (1969). Binet eventually developed successful IQ tests derived from tests measuring comprehension, knowledge, and acquired skills.…”
Section: Natural Abilities and Other Stable Characteristicsmentioning
confidence: 99%
“…Binel (Varon, 1935) slarted oul using tests of basic perceptual and cognitive capacities to measure IQ, but found large practice effects, which were later documented by Gibson (1969). Binet eventually developed successful IQ tests derived from tests measuring comprehension, knowledge, and acquired skills.…”
Section: Natural Abilities and Other Stable Characteristicsmentioning
confidence: 99%
“…Both of them, Binet and Kraepelin, were inspired by the application of the idea of individual difference to exceptional groups of people. Kraepelin was mainly interested in those who had an abnormal mental life, while Binet was interested in extraordinary people who, for example, were distinguished in their ability to play chess blindfold or to conductmental calculations (Varon 1935).…”
Section: Individual Psychologymentioning
confidence: 99%
“…In other words, what was once perceived to be the most important achievement in all the history of psychology or even beyond, does not even rank among the 100 most eminent events in the 20th century. Many historians believe that neglecting Binet's role in the development of psychodiagnostic methods is unjust (Cicciola, Foschi, Lombardo 2014, Nicolas, Levine 2012, Varon 1935, 1936, Wolf 1964. Similarly, there is probably no excuse for overlooking the role and impact that Kraepelin and Oehrn exerted on the emergence of individual psychology.…”
Section: Individual Psychologymentioning
confidence: 99%
“…Contrary to expectation, the search for measures of basic capacity that correlate with performance in complex tasks of everyday life has been mostly unsuccessful. A long time ago, Binet (Varon, 1935) sought to design a test of general intelligence, but after considerable effort he gave up on measuring basic processes and capacities and turned to measures of complex comprehension and retrieval of knowledge. Binet found that with a moderate amount of practice on the tasks measuring basic capacities, substantial improvement resulted, which decreased differences between subjects of low and high intelligence.…”
Section: A the Quest For General Processesmentioning
confidence: 99%